Effect of Sapodilla (Manilkara zapota) Addition on the Organoleptic and Chemical Properties of Brownies - Nurul Ramazani; Ichsan Ichsan; Alfridsyah Alfridsyah (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2026)
Sapodilla (Manilkara zapota) is a tropical fruit with considerable potential for value-added food development because of its nutritional content and distinctive sensory characteristics. However, its application in bakery products remains limited. This study aimed to evaluate the effect of different levels of sapodilla addition on the sensory and chemical properties of steamed brownies. An experimental study was conducted using a completely randomized design (CRD) with a single factor consisting of three levels of sapodilla addition (100 g, 150 g, and 200 g), each performed in triplicate, resulting in nine experimental units. Brownies were evaluated for sensory attributes (color, taste, aroma, and texture) using a hedonic test, while proximate analysis was performed to determine moisture, ash, protein, fat, and carbohydrate contents. The results showed that sapodilla addition significantly affected the taste of the brownies (p < 0.05) but had no significant effect on color, aroma, or texture (p > 0.05). Likewise, different levels of sapodilla addition did not significantly influence the carbohydrate, protein, fat, ash, or moisture contents of the brownies (p > 0.05). These findings indicate that sapodilla can be incorporated into steamed brownies to improve taste acceptability without adversely affecting other sensory attributes or the overall nutritional composition, highlighting its potential as a locally available ingredient for value-added bakery products.